Association between glyphosate exposure and cardiovascular health using “Life’s Essential 8” metrics in US adults - Yuankang Zhu; Zhenlin Yang; Yuhao Chen; Lingzi Qian; Changning Hao; Liangshi Hao; Boshen Yang; Junli Duan (Ecotoxicology and Environmental Safety)
Background: Glyphosate, as one of the most widely used herbicides worldwide, has been reclassified as a potential carcinogen and linked to multiple health problems. Recent data from animal experiments have proved its potential cardiovascular toxicity. However, whether glyphosate exposure influences human cardiovascular health at the population levels remains unknown. This study aims to elucidate the correlation between glyphosate exposure and Cardiovascular Health (CVH) by utilizing comprehensive Life's Essential 8 (LE8) metrics. Methods: Data from 2842 participants, approximating 155.24 million U.S. adults, from 2013 to 2018 in National Health and Nutrition Examination Survey were analyzed. The association between natural logarithm (ln)-transformed glyphosate exposure in urine and CVH was examined using weighted linear regression and restricted cubic spline (RCS) models. Mediation analysis was used to determine potential mediators correlated with glyphosate and CVH. Further subgroup analysis and sensitive analysis were conducted to confirm the results. Results: In fully adjusted models, the total CVH score decreased by 1.33 points for every unit increase in continuous ln-transformed glyphosate [β = -1.33, 95 % confidence interval (CI) (-2.25, −0.41)]. There was a negative correlation between the total CVH score and the lowest quantiles of ln-transformed glyphosate (Q1), Q2, Q3, and Q4 with p for trend < 0.05. A non-linear relationship between glyphosate and total CVH emerged (p for non-linear<0.001, p for overall = 0.003), and no safe threshold of glyphosate was observed. Serum insulin was an important mediator in the adverse effects of glyphosate on CVH with an 18.73 % mediation proportion. Moreover, higher serum insulin levels and higher homeostasis model assessment of insulin resistance were associated with higher glyphosate exposure but negatively correlated with total CVH score. Conclusions: Glyphosate exposure may pose a risk to cardiovascular health at the population levels, with elevated serum insulin levels acting as a crucial mediating element. Further studies are required to investigate the safe threshold and underlying mechanism of glyphosate impairment.